2015
DOI: 10.1002/2015jd023245
|View full text |Cite
|
Sign up to set email alerts
|

FDTD simulation of LEMP propagation over lossy ground: Influence of distance, ground conductivity, and source parameters

Abstract: We have computed lightning electromagnetic pulses (LEMPs), including the azimuthal magnetic field H φ , vertical electric field E z , and horizontal (radial) electric field E h that propagated over 5 to 200 km of flat lossy ground, using the finite difference time domain (FDTD) method in the 2-D cylindrical coordinate system. This is the first systematic full-wave study of LEMP propagation effects based on a realistic return-stroke model and including the complete return-stroke frequency range. Influences of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…They studied influences of the return‐stroke speed (ranging from c /2 to c ), current risetime (ranging from 0.5 to 5 μs), and ground conductivity (ranging from 0.1 mS/m to ∞) on electric and magnetic field waveforms. Aoki et al () disregarded the presence of conducting atmosphere, because they only considered the ground wave.…”
Section: Introductioncontrasting
confidence: 74%
See 2 more Smart Citations
“…They studied influences of the return‐stroke speed (ranging from c /2 to c ), current risetime (ranging from 0.5 to 5 μs), and ground conductivity (ranging from 0.1 mS/m to ∞) on electric and magnetic field waveforms. Aoki et al () disregarded the presence of conducting atmosphere, because they only considered the ground wave.…”
Section: Introductioncontrasting
confidence: 74%
“…Qin et al (2017) concluded that their model is adequate for predicting lightning sky waves in VLF/LF bands at distances up to 1,000 km. Aoki, Baba, and Rakov (2015) examined propagation of vertical electric field, azimuthal magnetic field, and horizontal (radial) electric field over 5 to 200 km of flat lossy ground, using the FDTD method in the 2-D cylindrical coordinate system. In contrast to previous FDTD studies, their model employed a travelingwave-type return-stroke model and covered nearly complete return-stroke frequency bandwidth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These choices were made considering that ground wave features are sharper than those of sky waves, and therefore, ground wave signals require higher-frequency components to adequately reconstruct their features. Lowpass filtering to an upper frequency response of 700 kHz maintains all the observed salient features of the time domain ground wave that has had its high-frequency content attenuated in propagating over 209 km of Florida soil [e.g., Uman et al, 1976;Aoki et al, 2015;Jiang et al, 2016]. In our data, the received ground wave 10-90% risetime exceeds 1 μs, similar to the experimental over-ground data of Uman et al [1976] for natural subsequent strokes recorded at 200 km in Florida, whereas natural subsequent stroke ground waves propagating over salt water of relatively high conductivity, expected to produce significantly less propagation attenuation, exhibit submicrosecond risetimes [Weidman and Krider, 1980].…”
Section: Electric Field Measurement 209 Km South (Uf Station)mentioning
confidence: 99%
“…Recent studies show that the amplitude and phase perturbation for VLF signals have a complicated relationship with the ionospheric D region parameters. The propagation of the VLF signal between the Earth ground surface and the lower ionosphere can be affected by many factors, such as the propagation distances (Aoki et al, ; Azadifar et al, ; Tran et al, ), the attenuation due to the ground conductivity (Aoki et al, ; Tran et al, ), the electron and neutral particle densities (Lay and Shao, ; Lay et al, ; Marshall, ), the Earth curvature (Tran et al, ) and the presence of the geomagnetic field (Lay et al, ; Shao et al, ).…”
Section: Introductionmentioning
confidence: 99%